2006
DOI: 10.1136/oem.2005.023333
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and paternal occupational exposure to agricultural work and the risk of anencephaly

Abstract: These results support the hypothesis of the effect of maternal exposure to agricultural work on anencephaly and suggest that exposure of the father to pesticides in the periconceptional period or prior to this can also increase the risk of having an anencephalic child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 46 publications
5
46
0
4
Order By: Relevance
“…This supports other studies that reported an association between agricultural work and/or exposure to pesticides experienced by the father, or the mother, or both; and different adverse reproductive effects such as congenital malformations in general [23][24][25], cleft lip and palate [26][27], musculoskeletal defects [28], limb reduction defects [29][30], and central nervous system defects [31][32][33]. Environmental or occupational exposure to pesticides may cause alterations in the male gametes prior to conception, as well as embryonic damage or feto-placental complex.…”
Section: Discussionsupporting
confidence: 77%
“…This supports other studies that reported an association between agricultural work and/or exposure to pesticides experienced by the father, or the mother, or both; and different adverse reproductive effects such as congenital malformations in general [23][24][25], cleft lip and palate [26][27], musculoskeletal defects [28], limb reduction defects [29][30], and central nervous system defects [31][32][33]. Environmental or occupational exposure to pesticides may cause alterations in the male gametes prior to conception, as well as embryonic damage or feto-placental complex.…”
Section: Discussionsupporting
confidence: 77%
“…Women with a neural tube defect-affected baby were also more likely to report living in the proximity to cultivated fields than control women [17]. Another study among Mexican women reported that working in agriculture around the time of conception was associated with a greater risk of anencephaly in the offspring [22]. More recently, a positive association has been found between placental concentrations of different organochlorine observed in urban microregions, suggesting that pesticide exposure may play an important role in the geographical distribution of mortality from congenital malformations only in rural areas.…”
Section: Ijomeh 2014;27(3) 482mentioning
confidence: 96%
“…Maternal exposure to domestic pesticides during the 1st trimester of pregnancy was associated with transposition of the great arteries in the offspring, particularly for exposure to herbicides and rodenticides [24]. Several other epidemiological studies also reported associations between pesticide exposure and a variety of congenital anomalies, particularly in the offspring of agricultural workers, in infants born to women living in the proximity of pesticide application areas or in babies conceived in a particular season [3,[16][17][18]20,22,23,36]. In Brazil, one study found a greater risk of congenital defects in births to parents exposed to pesticides at work or due to proximity to an application area [20].…”
Section: Ijomeh 2014;27(3) 482mentioning
confidence: 97%
“…Men working in the agriculture sector are at more than tenfold increased risk of infertility in comparison to those in other occupations [80]. Exposure of the father to pesticides during the preconception period or prior can also increase the risk of having anencephalic child [81].…”
Section: Pesticides and Other Polychlorinated Hydrocarbonsmentioning
confidence: 99%